Renal denervation: tips and tricks to perform a technically successful procedure - Bertog, Stefan; Blessing, Erwin; Vaskelyte, Laua; Hofmann, Ilona; Id, Dani; Sievert, Horst (EuroIntervention, 2013)
To most practitioners involved in catheter-based interventions, percutaneous renal sympathetic denervation is not technically challenging. However, under specific clinical circumstances (e.g., renal insufficiency) or when faced with more complex abdominal aortic anatomy (e.g., tortuosity) some procedural tips may come in handy. Here we review the equipment, antiplatelet and anticoagulant strategy as well as the procedural technique, including tips and tricks for the successful performance of catheter-based renal denervation. Among other topics, carbon dioxide angiography and brachial artery access are discussed.
Gesehen am 24.11.2020